Possible Biogeophysical Effects of Cultivated Land Conversion in Northeast China in 2010–2030 - Haiming Yan; Jinyan Zhan; Juan Huang; Tengteng Zhai (Advances in Meteorology)
There will be substantial cultivated land change in China as the society strives to meet the growing food demands, which will greatly influence the future climate. This study analyzed the possible biogeophysical effects of cultivated land change on the climate in Northeast China during 2010–2030 on the basis of simulation with the Weather Research and Forecast (WRF) model. Scenario analysis was first carried out on the possible changing trends of cultivated land. Then the climate effects of the cultivated land change were analyzed on the basis of the simulation with the WRF model. The simulation results indicate that the total cultivated land area in Northeast China will decrease during 2010–2030, mainly converting into urban and built-up land and forests due to the urbanization and governmental policies. Besides, the cultivated land change will lead to the increase of the sensible heat flux in the regions where a lot of cultivated land will change into urban and built-up land, while it will make the latent heat flux increase in the regions where the cultivated land will be mainly converted into forests through influencing the evapotranspiration. All these results can provide theoretical support for implementing the future land management in Northeast China.